Treatment of skin lesions in newborn children: meeting the needs of nursing staff - Santos,Simone Vidal (2014)
Objective To understand, together with nursing staff, the care needed to treat skin lesions in newborn children hospitalized in a neonatal unit. Method Qualitative research, of the convergent care type. The data was collected through semi-structured interviews, which were conducted from November to December 2012, in the neonatal unit of a hospital in southern Brazil. The participants were four auxiliary nurses, six nursing technicians and four nurses. Results The following three categories were designated: questions about what can be used in relation to newborn children; hospitalization can cause lesions on the skin of newborn children; and knowledge about care promotes professional autonomy. Conclusion There is an urgent need for staff to know more about the treatment of skin lesions, which would provide safer care for newborn children and would also support the autonomy of professional nurses in providing that care.